Literature and Sociology: A Siamese Twins’ Journey from Entwined to Estranged - Asmaa Ramil (Skad)
This paper traces the key moments that shaped the perceptions of the literary arts and their epistemic relationship with systematic social study in Western thought. Following a chronological order, spanning from antiquity to the modern era, it adopts a conceptual-history approach. This comprehensive scope enables the analysis of different watersheds in religion, philosophy, science and social thought. As Enlightenment rationality ascended, the mystical insights of poetry were derided as irrational fancies. Accordingly, pioneer sociologists – in their endeavour to achieve academic legitimacy and authority – distanced themselves from the suspect influence of belletristic styles. Before long, sociology disavowed literature entirely, denying its own foundation in literary commentary and critique. However, the emergence of new paradigms (deconstructionism, post-structuralism, etc.) destabilised this institutional estrangement. The study reveals that literature has been intertwined with the social studies in general, and the genesis and development of sociology in particular. It argues that both remain inextricably linked in their endeavours to illuminate the human condition. This research ultimately postulates that the fluidity between these disciplines encourages a holistic understanding of society, fostering creativity, empathy, scientific inquiry and critical thinking.